FORM AND FACTORS CAUSING THE MORAL DECADENCY OF THE MILLENIAL GENERATION IN SOCIAL LIFE OF COMMUNITIES - Fazillah, Nur; Fadli, Dastur (PT. Antis International Publisher, 2024)
Moral decadence in the current millennial era occurs when the flow of modernization is able to provide everything that has an impact on the moral decline of the Indonesian population, especially among the youth. The problem of the moral crisis experienced especially among the youth has spread, and can threaten the future of the nation. Planting characters in the family environment is not enough in moral construction because when they grow up the child will find a new environment that will also shape his personality. Planting character in the family environment will become the foundation for further character, but not a few experience decline due to the influence of this new environment. In constructing the morals of the nation's generation, three elements of the state which include society, government and the private sector must build synergy in creating Indonesia's golden generation. As for the government, with its duties and functions as policy makers, it can create educational regulations that are oriented towards instilling noble values, as well as building the character of young Indonesian intellectuals. Character building in formal education institutions has not achieved the expected output. Much of this character education is in the form of theory, without any room for the implementation of character or moral values. Furthermore, the presence of Human Rights (HAM) also becomes a pathology in character building, because Human Rights indirectly limit the domination of educators over students